2023
DOI: 10.1007/jhep04(2023)110
|View full text |Cite
|
Sign up to set email alerts
|

The mixed-state entanglement in holographic p-wave superconductor model

Abstract: In this paper, we investigate the mixed-state entanglement in a model of p-wave superconductivity phase transition using holographic methods. We calculate several entanglement measures, including holographic entanglement entropy (HEE), mutual information (MI), and entanglement wedge cross-section (EWCS). Our results show that these measures display critical behavior at the phase transition points, with the EWCS exhibiting opposite temperature behavior compared to the HEE. Furthermore, we explore the behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Holographic QCD [28][29][30][31][32][33][34] and holographic condensed matter theory [35,36] research has found that, as non-local observables, entanglement properties can also serve as effective order parameters for various phase transitions. These include transitions such as metal-insulator phase transitions [36][37][38], superconducting phase transitions [39][40][41][42], deconfinement phase transitions [43][44][45][46][47][48][49][50], and phase transitions related to quark-gluon matter [28,32]. Mutual information [51][52][53] and entanglement of purification [32,33] have also been utilized as order parameters in several studies characterizing phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Holographic QCD [28][29][30][31][32][33][34] and holographic condensed matter theory [35,36] research has found that, as non-local observables, entanglement properties can also serve as effective order parameters for various phase transitions. These include transitions such as metal-insulator phase transitions [36][37][38], superconducting phase transitions [39][40][41][42], deconfinement phase transitions [43][44][45][46][47][48][49][50], and phase transitions related to quark-gluon matter [28,32]. Mutual information [51][52][53] and entanglement of purification [32,33] have also been utilized as order parameters in several studies characterizing phase transitions.…”
Section: Introductionmentioning
confidence: 99%